PENGARUH UMUR SIMPAN DAN SKARIFIKASI TERHADAP VIABILITAS BENIH SIRSAK (Annona muricata L) - Noflindawati Noflindawati (Jurnal Floratek, 2014)
Seed viability is influenced by genetic factors, seed ages, and the physical properties of the seed itself. This research was aimed at determining effects of seed storage life and scarification on seed viability of soursop. The experiment was conducted from March to May 2013 in Sumani Experimental Tropical Fruit Research Institute Solok, West Sumatra. The experiment was arranged in a completely randomized design (CRD) with four replications. The study consisted of two sets of treatments. The first was seed storage, i.e., 6 months storage and without storage and the second one was seed scarification, i.e. without scarification and scarified seeds. The results showed that the soursop seeds that were stored for six months decreased germination rate (GR) from 82.5% to 65.0% and decreased maximum growth potential (MGP) from 86.0% to 70.5% but did not decrease vigor index and seedling height. In addition, seed scarification lowered vigor index and dry weight of normal seedling. Unscarified seeds did not lower GR and this suggests that scarification by cutting the base of the seeds is not effective for soursop seed.